'Silvery singing voices': Moroccan Manchester and the Puzzle of Richard Wright. Issue 1 (2nd January 2022) - Rose, Martin
ABSTRACT: This essay is an attempt to reconstruct a little of the history of the Moroccan merchant community in Manchester, and to establish both who Wright actually was, and how his collaboration with those expatriate Fassi cotton-traders gave birth to – or perhaps simply perpetuated – the Moroccan théière . It will then trace, insofar as is possible, the evolution of the reputation and manufacture of 'Wright' silver plate down to our own day. Finally, It will look briefly at the mythology that has grown up around Richard Wright in Morocco, inhabiting as he does the odd paradox described by Abdelahad Sebti: The history [of tea in Morocco] which is really rather brief, evokes in the collective imagination the idea of an immemorial tradition. The illusion of tea's being rooted deep in the country's past; but also the illusion of [Morocco's] having been the foremost champion of the drink in the world. (Sebti 1999, 141) He is an intriguing emblem of the cultural entanglement of Morocco and Britain, more potent today than in his own lifetime.